A Time Series Analysis of Labour Absence in Australia - Kenyon, Peter; Dawkins, Peter (The Review of Economics and Statistics, 1989)
The authors find evidence from Australian time-series data supporting two hypotheses about the determination of labor absence. First, labor absence modeled in a utility-maximizing framework that stresses the opportunity cost of labor absence receives considerable support from the data. Variables that change the slope and/or shift the budget constraint facing workers affect labor absence. Secondly, the authors find tentative evidence that coercive or difficult work environments, which apparently affect job satisfaction, adversely affect labor absence. In particular, it appears that labor absence is a leading indicator of a deteriorating industrial relations environment characterized by increased industrial disputation. Copyright 1989 by MIT Press.